Intracranial Pressure Monitoring in Patients with Severe Traumatic Brain Injury: A Cohort Study with Paired Analysis - Torres, Gabriel Saboia de Araújo; Paiva, Wellingson Silva; Amorim, Robson Luís Oliveira de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Introduction Intracranial hypertension continues to be the most frequent cause of death in patients with traumatic brain injury (TBI). Thus, invasive monitoring of intracranial pressure (ICP) is a very important tool in neurointensivism. However, there is controversy regarding ICP monitoring and prognosis.Objectives To evaluate whether there is a difference in mortality between patients with severe TBI who underwent invasive ICP monitoring compared with those who did not undergo such procedure.Methodology This is a unicentric study in the prospective cohort mode. A total of 316 patients with severe TBI were evaluated and, out of these 316 individuals, 35 were submitted to ICP monitoring. All clinical data were evaluated by the Tertiary Hospital Neurosurgery team in the city of São Paulo.Results Of the total cohort, 35 (11%) patients underwent ICP monitoring, while 281 did not. Comparing the 2 groups, there was no difference in terms of early mortality between patients who were submitted to monitoring and those who were not (34.3 versus 14.3%; p = 0.09); there was also no difference in terms of hospital mortality (40 versus 28.5%; p = 0.31) or intensive care unit (ICU) length of stay (16.10 days, 95% confidence interval [CI]: 10.6–21.6; versus 20.60 days, 95%CI: 13.50–27.70; p = 0.31).Conclusions In this cohort, we did not identify differences in mortality or in duration of hospitalization between patients with ICP monitoring and those exclusively with clinical-radiological evaluation. However, further national co-operative studies of services using ICP monitoring are needed to achieve results with greater generalization power.
Keywords: intracranial pressure; hospital mortality; intracranial hypertension; brain injuries; traumatic